PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE FORMULATE SHARE LISTEN CREATE TERHADAP KEMAMPUAN LITERASI MATEMATIS PESERTA DIDIK KELAS VIII - Saskiaredina, Saskiaredina (Departemen Matematika, 2023)
Mathematical literacy has a significant posision in mathematics learning, because this knowledge be able to formulate, employ, and interpret mathematic in a variety of contexs. Several research have shown that ability is still low. This also happened at SMP Negeri 1 Payakumbuh best on the test result given to students class VIII. One solution to improve this ability is apply the Formulate Share Listen Create (FSLC) cooperative learning model. The aim of this research was to see the effect of the FSLC model on the mathematical literacy ability in class VIII. The type of research is a pre-experiment with one-shot case study design. The instruments of this research are mathematical literacy competence test and quiz. Data analysis shows that students mathematical literacy ability after applying the FSLC model increases. Keywords– Formulate Share Listen Create, Mathematics Literacy Ability, One Shot Case Study